SPACA3gene variants in a New Zealand cohort of infertile and fertile couples - Prendergast, Deborah; Woad, Kathryn J.; Chamley, Lawrence W.; Holland, Olivia J.; Shelling, Andrew N. (Taylor & Francis, 2014)
SPRASA (also referred to as SLLP1) is a protein identified in the acrosome of human sperm and encoded by the gene SPACA3. SPRASA is associated with sperm-oocyte recognition and binding, and may play a role in fertility. In order to determine whether variants in the SPACA3 gene are associated with human infertility, we undertook a genetic analysis of 102 infertile and 104 fertile couples. Three gene variants were identified using PCR-based DNA sequencing; 1) an insertion of TGC within a quadruple tri-nucleotide (TGC) repeat region in the 5’ untranslated region (UTR) (g.–22TGC(4_5), 2) a guanine to adenosine transition at position 239 (c.239G> A) resulting in a non-synonymous amino acid substitution from cysteine to tyrosine (p.C80Y) at position 80 in the putative transmembrane region, and 3) a novel nucleotide variant (c.691G> C) located in the 3’UTR. A functional effect of the g.–22TGC (4_5) was confirmed by a luciferase expression assay, while the effects of the variants c.239G> A and c.691G> C were predicted using in silico analysis. Although the frequencies of these variants were not significantly different between the infertile and fertile populations, we present evidence that the variants could affect the expression levels or function of SPRASA, thereby affecting a couple's fertility. Larger populations, especially individuals/couples with unexplained infertility, need to be screened for these variants to validate a relationship with fertility.